A Unidirectional Transition from Migratory to Perivascular Macrophage Is Required for Tumor Cell Intravasation - Esther N. Arwert; Allison S. Harney; David Entenberg; Yarong Wang; Erik Sahai; Jeffrey W. Pollard; John S. Condeelis (Cell Reports, 2018)
Summary: Tumor-associated macrophages (TAMs) are critical for tumor metastasis. Two TAM subsets support cancer cell intravasation: migratory macrophages guide cancer cells toward blood vessels, where sessile perivascular macrophages assist their entry into the blood. However, little is known about the inter-relationship between these functionally distinct TAMs or their possible inter-conversion. We show that motile, streaming TAMs are newly arrived monocytes, recruited via CCR2 signaling, that then differentiate into the sessile perivascular macrophages. This unidirectional process is regulated by CXCL12 and CXCR4. Cancer cells induce TGF-β-dependent upregulation of CXCR4 in monocytes, while CXCL12 expressed by perivascular fibroblasts attracts these motile TAMs toward the blood vessels, bringing motile cancer cells with them. Once on the blood vessel, the migratory TAMs differentiate into perivascular macrophages, promoting vascular leakiness and intravasation. : Tumor-associated macrophages (TAMs) are essential for metastasis. Arwert et al. show that, following extravasation, monocytes initially become motile TAMs. Tumor-derived TGF-β then induces CXCR4 on TAMs, stimulating them to migrate toward CXCL12-expressing perivascular fibroblasts. Once adjacent to blood vessels, TAMs differentiate into metastasis-assisting perivascular TAMs. Keywords: tumor associated macrophages, TAMs, TGF beta, breast cancer, metastasis, CXCR4, CCR2, TMEM, Mena